Pengaruh Word Of Mouth dan Kualitas Produk Terhadap Keputusan Pembelian MS Glow Dengan Gaya Hidup Sebagai Variabel Intervening - Manullang, Winda Chairani; Gultom, Dedek Kurniawan (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2024)
This study aims to determine the effect of word of mouth and product quality on the purchasing decisions of Ms Glow with lifestyle as an intervening variable in FEB UMSU students, either directly or indirectly. The data analysis technique of this study used statistical analysis, namely the least squares partial equation model (PLSSEM). The results of the study show that there is an influence of Word of Mouth on Purchasing Decisions in UMSU Faculty of Economics and Business students. There is no effect of Product Quality on Purchasing Decisions for UMSU Faculty of Economics and Business Students. There is an influence of Lifestyle on Purchasing Decisions in UMSU Faculty of Economics and Business Students. There is the influence of Word of Mouth on Lifestyle in UMSU Faculty of Economics and Business Students. There is an influence of Product Quality on Lifestyle in UMSU Faculty of Economics and Business Students. There is an influence of Word of Mouth on Job Satisfaction Purchasing Decisions as an intervention variable for Students of the Faculty of Economics and Business UMSU. There is an influence of Product Quality on Purchase Decisions with Lifestyle as an intervention variable for UMSU Faculty of Economics and Business Students